An assessment of volatility transmission in the Jamaican financial system - Hurditt, Percival ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2004)
Applies the GARCH-BEKK procedure to the returns from the Jamaican bond, foreign exchange and stock markets in order to estimate the magnitude of the common market and cross-market volatility transmission.